Keadilan Gender dan Hak-hak Reproduksi di Pesantren - Fitria, Maya; Helmi, Avin Fadilla (Jurnal Psikologi, 2011)
This study was intended to understand how the phenomenon of gender equity and reproductive rights in pesantren using the theoretical framework of attitude. The research wasconducted in a qualitative approach through a case study method. Sources of data consisted of 10 interviewed subjects, 18 FGD subjects, and survey of 327 subjects. Subjects were varyingfrom pesantren’s supervisor, teacher, manager and doctor of pesantren’s Community Health Center, and santri itself. Data was also obtained from the observation of the supervisors’behaviors and the pesantren’s environment. Subjects tended to agree in distinguishing the male and female gender role based on what’s happening, different from the religious teachingsthey learned which tended to be gender fair. Regarding with women reproductive cases, subjects tended to be gender biased based on the interpretation of religious texts although theyadmitted that it was hard to be manifested in behavior, example: prefering monogamous marriage,never beating women, and not promoting early marriage. Subjects agreed andunderstood that women had different, and yet more complex anatomical processes and functions, however their health service were just considered the same as men.